The effectiveness of EC policies to move freight from road to rail: Evidence from CEE grain markets - Russell W. Pittman; Monika Jandová; Marcin Król; Larysa Nekrasenko; Tomáés Paleta (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2019)
The European Commission years ago adopted a policy of encouraging the substitution of motor carrier haulage of freight with rail and water carrier haulage, as part of its "green" agenda of reducing fuel consumption, emission of pollutants, carbon intensity, and road congestion. Regarding railway freight in particular, one policy tool that the Commission has emphasized for this purpose is the restructuring of the rail sectors of member countries through the creation of competition for the incumbents by new train-operating companies (TOC's) - on its face a less obvious policy choice than alternatives such as Pigouvian pricing measures or infrastructure subsidies. This paper focuses on one important commodity group - grain - in three EC member states and one non-member state - Poland, the Czech Republic, Slovakia, and Ukraine - to examine the degree to which increased rail competition has been associated with increases in rail's modal share, and more broadly to learn what appear to be the binding constraints to increases in rail's share. Such constraints seem more closely related to shortages in infrastructure capacity than to a lack of competition among TOC's. This suggests that other "models" of railway restructuring may be more effective in easing this constraint.
Keywords: L92; Q58; R11; R41; R42; R48; 330; European Commission; railways competition; environmental protection; open access; motor carriers; intermodal competition